Effectiveness of The Discovery Learning Model based Ethnoscence Tempoyak on Acid Base Subject to Improving Student's Critical Thinking Skills - Reni Junisa; Sunyono; Gamilla Nuri Utami (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
The aim of this study is to analyze the effectiveness of the discovery learning model, which is grounded in Tempoyak ethnoscience, in the context of acids and bases, with regard to fostering critical thinking among students. The study was conducted with 11th-grade students at SMA Muhammadiyah 2 Bandar Lampung during the 2025/2026 school year, with class XI A selected as the experimental group and class XI D as the control group. These groups were determined through a cluster random sampling. A quasi-experimental method with a pretest and posttest design was used for the control group. Data analysis was performed using n-Gain, the t-test for independent samples, and the calculation of effect sizes. The results show that the mean n-Gain values for the experimental and control classes are 0.41 and 0.35, respectively. The t-test for independent samples reveals a significant difference between the two groups, while the effect size of 0.95 indicates a substantial effect. Thus, the discovery learning model based on ethnoscience Tempoyak regarding acids and bases proves effective in improving students’ critical thinking skills.